Total intravenous anaesthesia in dogs and cats with propofol and it’s associations (Revista de Ciências Agroveterinárias, 2007)
Total intravenous anesthesia (TIVA) is a technique that has been used more frequently in small animals. Its use has been motivated by the introduction of new drugs with shorter and faster onset action, and by the improving of the infusion bombs. TIVA presents some advantages such as: no environment pollution; it does not demand great investment in the acquisition of specific equipment as for the accomplishment of inhalatory anesthesia; hemodynamic stability and a reduction in the adrenergic response by the surgical stimulation. On the other hand, it also presents some limitations such as: the need of a vein catheterization for the infusion; it’s contraindicated in animals that possess hepatic or renal failure; and it has the necessity of different infusion bombs for each drug used. This technique can be carried out using bombs or equips, in bolus or for continuous rate infusion (CRI) and more recently through modern techniques of targetcontrolled infusion (TCI). Propofol is the most used hypnotic agent drug, being associated with analgesic agents as opioids (extreme-shortness duration), ketamine and/or lidocaine. Differently of what happens with dogs, there is little information about the pharmacokinetic of propofol in cats, which have important differences regarding to the biotransformation of some drugs. Some studies have been carried out in dogs and cats aiming to evaluate the effects caused by propofol and the other agents in CRI, but more studies are still needed, so that these protocols can be used with security in anesthetic practice as an alternative to the inhalatory anesthesia.
Keywords: total intravenous anesthesia; dogs; cats; propofol.